Modernity and mass culture - Naremore, James; Brantlinger, Patrick 1941-
Modernity and Mass Culture is a wide-ranging analysis of the relationship between industrialization, democracy, and art in the twentieth century. US and British scholars discuss the interaction between "high," "popular," and "mass" art, showing how Western culture as a whole is affected by the transition from the modern to the postmodern era. Their essays deal with advertisements, films, recorded music, television, and mass-market literature. Among the topics addressed are assembly-line manufacture, home entertainment, popular reception, avant-garde theory, "post-feminist" fiction, and "retro" style.